2006
DOI: 10.1152/ajpheart.01243.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective mechanisms ofPrunus cerasus(sour cherry) seed extract against ischemia-reperfusion-induced damage in isolated rat hearts

Abstract: Cardioprotective mechanisms of Prunus cerasus (sour cherry) seed extract against ischemia-reperfusion-induced damage in isolated rat hearts. Am J Physiol Heart Circ Physiol 291: H1329 -H1336, 2006. First published April 14, 2006 doi:10.1152/ajpheart.01243.2005The effects of kernel extract obtained from sour cherry (Prunus cerasus) seed on the postischemic cardiac recovery were studied in isolated working rat hearts. Rats were treated with various daily doses of the extract for 14 days, and hearts were then is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 68 publications
4
57
0
1
Order By: Relevance
“…Previous work by the authors has demonstrated potent cardioprotective properties of HO-1 (10,11). These outcomes are consistent with many investigations demonstrating that phytochemical HO-1 induction correlates with improved prognoses of many diseases (12).We have previously shown that SCSE strongly protects the heart against I/R injury, as revealed by enhanced postischemic left ventricle function, reduced infarct size, and decreased apoptosis in rat hearts subjected to I/R-injury (13). Recent animal studies also demonstrated SCSE-mediated enhancement of SCSE-mediated adaptive response in hearts of hypercholesterolemic rabbits (14).…”
Section: A C C E P T E Dsupporting
confidence: 89%
See 2 more Smart Citations
“…Previous work by the authors has demonstrated potent cardioprotective properties of HO-1 (10,11). These outcomes are consistent with many investigations demonstrating that phytochemical HO-1 induction correlates with improved prognoses of many diseases (12).We have previously shown that SCSE strongly protects the heart against I/R injury, as revealed by enhanced postischemic left ventricle function, reduced infarct size, and decreased apoptosis in rat hearts subjected to I/R-injury (13). Recent animal studies also demonstrated SCSE-mediated enhancement of SCSE-mediated adaptive response in hearts of hypercholesterolemic rabbits (14).…”
Section: A C C E P T E Dsupporting
confidence: 89%
“…Briefly, following removal of external shell components, the dried seed kernels were ground and extracted with n-hexane, followed by vacuum evaporation and defatting to yield a standardized extract suitable for use as a feed supplement (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…grape juice and fortified wine or other sources suggested to contain resveratrol, such as hops, which are present in beer [35], or cherries [36]. Nevertheless, our estimation of resveratrol intake might be acknowledged as sensitive on a population level, as the sources that were not used contain a low concentration of resveratrol [27,35,36] and/or are not widely consumed in the total population.…”
Section: Discussionmentioning
confidence: 99%
“…The extract was filtered through a clean cotton cloth, and then, solvent was evaporated using a rotary evaporator at 40°C temperature in vacuum. The extract doses were selected on the basis of experiments conducted in the university laboratory and earlier reports (17). Therefore, with regard to the effective doses of Prunus cerasus kernel extract in mice (250, 500, and 1000 mg/kg), the current study used the same doses considering the body weight of the mice rather than the base ME; thus, 2.5%, 5%, and 10% ME extracts were obtained.…”
Section: Extraction Proceduresmentioning
confidence: 99%